Analysis of the Effectiveness of Interactive E-Modules for OBE-Based History Learning Evaluation with a Team-Based Project Approach - Arfan Diansyah; Yushar Tanjung; Syahrul Nizar Saragih; Abd. Haris Nasution (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This study aims to analyze the effectiveness of the interactive e-module History Learning Evaluation based on Outcome-Based Education (OBE) with a Team-Based Project approach, and assess the feasibility of the developed product. This research is a development research using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research process begins with a preliminary study and needs analysis, design of the e-module prototype, validation by material experts and media experts, product trials on students, and testing the effectiveness of the e-module through learning outcome tests. Data collection techniques include questionnaires and tests, while data analysis is carried out descriptively quantitatively. The results show that the developed interactive e-module obtained a feasibility level of 77% based on the assessment of material experts and 72% based on the assessment of media experts, both of which are included in the feasible category. The effectiveness test results showed an increase in student learning outcomes, with an average score of 63.13 in the initial test increasing to 79.46 in the final test. Based on effectiveness criteria, the interactive e-module of History Learning Evaluation based on OBE with a Team-Based Project approach was declared effective in improving student learning outcomes. Thus, this interactive e-module is suitable and effective for use as supporting teaching materials for the History Learning Evaluation course.